Highly efficient solar-absorber composite material based on tetrapyridylporphyrin for water evaporation and thermoelectric power generation. Issue 45 (11th October 2022) - Zhang, Yifeng; Yan, Hanbing; Wang, Xuefeng; Zhang, Zhenyu; Liu, Fengchun; Tu, Shan; Chen, Xiufang
Abstract : Photothermal conversion materials based on tetrapyridylporphyrin (TPyP) were studied and were found to possess a polypyrrole macrocyclic framework (18π electrons), which makes them exhibit strong absorption in the 300–800 nm region and high photothermal conversion. Abstract : Photothermal materials based on organic small molecules have the characteristics of structural diversity and easy modification for solar-driven water evaporation and power generation technology. However, there still exist limitations, such as the utilization of solar energy and photostability. Therefore, it is the focus of current research to design organic photothermal materials with excellent photothermal stability, strong solar absorption capacity, and high photothermal conversion efficiency. Herein, photothermal conversion materials based on tetrapyridylporphyrin (TPyP) is studied, which possesses polypyrrole macrocyclic framework (18π electrons), which makes it exhibit strong absorption in the 300–800 nm region with high photothermal conversion. The interfacial-heating evaporation system based on polyurethane (PU) foam loaded with TPyP was prepared, whose solar-to-vapor conversion efficiency and vapor evaporation rate of PU + TPyP foam solar energy reached 56% and 0.81 kg m −2 h −1, respectively. In addition, TPyP-loaded solar evaporator equipped with abundant microchannels for water flow are integrated with thermoelectric devices, thus achieving an evaporation rate and voltage as high as 0.69 kg m −2 h −1 and 60 mV under 1 kW m −2 solar irradiation, respectively. The successful application of TPyP in water evaporation and power generation effectively addresses the difficulties faced in the process of using organic small molecule photothermal materials to solve the energy crisis.